DIGITAL PAYMENT TRANSFORMATION AND ITS IMPACT ON BANK PERFORMANCE AND STABILITY: THE CASE OF INDONESIA’S QRIS ADOPTION - Lintang Selviana Aswan; Rizal Ahmad Fauzi; Wita Juwita Ermawati (Fakultas Ekonomi dan Bisnis, Universitas Airlangga, 2026)
Introduction: This study investigates the impact of QRIS (Quick Response Code Indonesian Standard) adoption on the financial performance and stability of Indonesian banks during the 2020–2024, focusing on key indicators under varying macroeconomic conditions. Methods: A quantitative approach is applies panel data regression using the Common Effect Model to analyze the effects of the QRIS Index on performance indicators such as Return on Assets (ROA), Return on Equity (ROE), and Net Interest Margin (NIM), and the effects of QRIS Growth on financial stability indicators including Non-Performing Loans (NPL), Loan to Deposit Ratio (LDR), Capital Adequacy Ratio (CAR), and Z-score. Results: The QRIS Index has a positive and significant impact on all performance indicators, suggesting improved bank efficiency and profitability through digital payment integration. Conversely, rapid QRIS Growth is associated with a significant decline in financial stability, as indicated by increased credit and liquidity risks and reduced capital buffers. Macroeconomic variables such as inflation and the BI Rate also significantly influence the results. Conclusion and suggestion: QRIS adoption promotes profitability, its expansion must be accompanied by robust risk management and supervisory readiness to mitigate systemic vulnerabilities in the long term.